THE MARKETING STRATEGY INCREASING THE HOME OF THE CRACKUP INDUSTRY DURING THE COVID-19 PANDEMIC IN THE VILLAGE MUNJUL, TANAH SAREAL BOGOR - Tri Nuary, Agi; Azis Firdaus, Muhammad (LPPM Univ. Ibn Khaldun Bogor, 2022)
Indonesia's economic activities have been hampered by the COVID-19 pandemic. This news is very worrying for UKM players, and it really happened in early April 2020. If only established UKM went out of business, especially business actors who only entered the low-class home industry category. Many companies are forced to lay off workers or laborers. In order to generate income, not a few of the home industry is quite profitable, one of the home industry businesses that can be developed is the production of crackers. Crackers are snacks that are very familiar and favored by the community. The research methodology used in this research is qualitative. In collecting data, conducting observations and interviews with home industry business owners. The advantage of this business is quite large because it already has many regular customers and this business is quite well known by the public, the marketing strategy is carried out through google maps and also whattsup besides that they market the crackers to stalls that have become their customers and also market them to markets who are already subscribed